Orsós Ferenc professzor és a környezetvédelem - Mudrák, József (Gerundium, 2015)
FERENC ORSÓS AND ENVIRONMENT PROTECTION. he study connected to the rector’s proile aims to introduce the professor of forensic medicine in a diferent light than he is known for his political and scientiic career. It rather focuses on the unknown side of this outstanding man: a natural scientist nurtuting an unquenchable devotion to trees and forests. As the supervisor of the clinical grounds, he fought in numerous occasions with the head gardener and the Financial Department of the university for saving each tree, especially during the felling at the construction of the Main Building. He also did his best to impede the proliferation of cats on the grounds, since the cats were to blame for the dangerously decreasing number of songbirds.